Dewantara, J., Yuniana, R., Graha, A. S., Sastaman B, P., Kushartanti, B. W., Nasrulloh, A., Septianto, I., Suryadi, D., Ardian, R., Widodo, A., Ridwan, A., & Haidar, M. D. (2024). ¿Cuál es la eficacia de la combinación de masoterapia y terapia de calor en la amplitud de movimiento articular? Estudio experimental en pacientes con dolor de hombre (What is the effectiveness of the combination of massage therapy and heat therapy on joint range of motion? Experimental study in patients with shoulder pain). Retos, 57, 147–152. https://doi.org/10.47197/retos.v57.104224 - Retraction Retraction
Dewantara, J., Yuniana, R., Graha, A. S., Sastaman B, P., Kushartanti, B. W., Nasrulloh, A., Septianto, I., Suryadi, D., Ardian, R., Widodo, A., Ridwan, A., & Haidar, M. D. (2024). ¿Cuál es la eficacia de la combinación de masoterapia y terapia de calor en la amplitud de movimiento articular? Estudio experimental en pacientes con dolor de hombre (What is the effectiveness of the combination of massage therapy and heat therapy on joint range of motion? Experimental study in patients with shoulder pain). Retos, 57, 147–152. https://doi.org/10.47197/retos.v57.104224